PENGARUH DISIPLN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. PENTA VALENT CABANG LAMPUNG - Surnita, Dwi (Universitas Mitra Indonesia, 2024)
This study aims to determine the effect of work discipline and organizational culture on employee performance. The data used in this study is primary data obtained directly from the source. Namely through respondents who filled out a questionnaire. Analysis techniques carried out through valisity, reliability, classical assumptions, hypotheses and multiple liniear regression. Based on the results of the analysis, it can be concluded that simultaneously the influence of work discipline and organizational culture has a significant effect on employee performance. Thus to improve employee performance must pay attention to work discipline factors and organizational culture in its implementation.